Analisis Produktivitas Tenaga Kerja dan Pertumbuhan Ekonomi Indonesia - Ramayani, Citra; Aimon, Hasdi; Anis, Ali (Program Studi Magister Ilmu Ekonomi, 2012)
ABSTRACT This study aims to identify and analyze: 1) The influence of education, health, public investment and private investment on labor productivity in Indonesia. 2) The effect of government investment, private investment, inflation, exports, employment and labor productivity to economic growth in Indonesia. This research is ekspost facto to the annual quantitative secondary data that is in Indonesia in the timeframe between the years 1980-2009 by using the simultaneous analysis model that has been through the test prerequisites. The results of this study found that: 1) Education, health, public investment and private investment and partially simultaneous significant effect on labor productivity in Indonesia. The higher funding for education, health, high investment, more and more private investment invested in Indonesia will be the higher productivity of labor in Indonesia. 2) Public investment, private investment, inflation, exports, employment and labor productivity simultaneously significant effect on economic growth in Indonesia. While in Persia, private investment, inflation, exports, and labor productivity affect economic growth in Indonesia. More and more private parties who invest their capital in Indonesia, the low inflation, and increasing exports will be able to increase economic growth. Meanwhile, public investment and labor no significant effect on economic growth in Indonesia. High or low government investment and private investment does not affect the high or low economic growth in Indonesia. Policy implications of the results of this study were: 1) In an effort to increase labor productivity in Indonesia then the policy needs to be taken by the government is more concerned with education and health by increasing funding to improve the quality of human resources. 2) Efforts should be done next government in promoting economic growthÂ is to do development equitably, improve the bureaucracy in order to create a conducive investment climate to attract investors to invest in Indonesia, to maintain economic stability in order to avoid excessive inflation, improve the quality of human resources in order to produces a high output and export value. Key Word : Productivity, Economic Grow